ANCIENT TURKISH LANGUAGE AND KOYNE EVENT (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The research on the linguistic features of the "Golden Light" created by ER Tenishev sixty years ago still retains its significance in Turkic studies.  The research conducted by Professor N. Rakhmonov is important in the study of the work from the point of view of literature and linguistics.  His observations on the genre features of the "Oltun Yarug", on the integrity of the spirit and faith in the work are noteworthy  [2, 3-17].  It is also worth noting that his views on the continuation of the features of the ancient Turkic language of the V-VIII centuries in the "Oltun Yarug" are quite reasonable.  In particular, the lexical layer of the work is based on the coyote, which is a feature of the ancient Turkic language, as well as the legitimacy of the ancient Turkic language.